2017
DOI: 10.1111/febs.14021
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase stabilizes the binding of GlnR to nitrogen fixation gene operators

Abstract: Biological nitrogen fixation (BNF) is a high energy demanding process carried out by diazotrophic microorganisms that supply combined nitrogen to the biosphere. The genes related to BNF are strictly regulated, but these mechanisms are poorly understood in gram-positive bacteria. The transcription factor GlnR was proposed to regulate nitrogen fixation-related genes based on Paenibacillus comparative genomics. In order to validate this proposal, we investigated BNF regulatory sequences in Paenibacillus riogrande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
(121 reference statements)
2
12
0
Order By: Relevance
“…Our results are different from some reports that P . riograndensis SBR5 GlnR is mainly the dimeric form [ 14 ] and B . subtilis GlnR is mainly monomeric form [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are different from some reports that P . riograndensis SBR5 GlnR is mainly the dimeric form [ 14 ] and B . subtilis GlnR is mainly monomeric form [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with the reports that GS, in its feedback inhibited form, interacts with GlnR of P . riograndensis SBR5 [ 14 ] and GlnR and TnrA of B . subtilis [ 18 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A somewhat similar mechanism is present in Bacillus subtilis (Fisher and Wray, 2008 , 2009 ; Wray and Fisher, 2008 ). Also, work in Paenibacillus riograndensis showed that the binding of glnR to its targets is facilitated when glnR is complexed with a glutamine synthetase—again, upregulation of glnR may bypass the lack of glnA2 [Hauf et al, 2016 ; Fernandes et al, 2017 ].…”
Section: Discussionmentioning
confidence: 99%